2016
DOI: 10.18632/oncotarget.13522
|View full text |Cite
|
Sign up to set email alerts
|

A novel fully human anti-NCL immunoRNase for triple-negative breast cancer therapy

Abstract: Breast cancer is the most common cancer in women worldwide. A new promising anti-cancer therapy involves the use of monoclonal antibodies specific for target tumor-associated antigens (TAAs). A TAA of interest for immunotherapy of Triple Negative Breast Cancer (TNBC) is nucleolin (NCL), a multifunctional protein, selectively expressed on the surface of cancer cells, which regulates the biogenesis of specific microRNAs (miRNAs) involved in tumor development and drug-resistance. We previously isolated a novel hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Lastly, given its recombinant nature and inherent versatility [ 64 ], 4LB5 can be conjugated to other molecules or protein domains to boost its clinical efficacy (e.g., adding immunoreactive Fc domain or active RNAse enzyme [ 65 ]). In fact, scFv antibodies are currently being investigated in PCa to target cell surface molecules such as PSMA for diagnostic purposes [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, given its recombinant nature and inherent versatility [ 64 ], 4LB5 can be conjugated to other molecules or protein domains to boost its clinical efficacy (e.g., adding immunoreactive Fc domain or active RNAse enzyme [ 65 ]). In fact, scFv antibodies are currently being investigated in PCa to target cell surface molecules such as PSMA for diagnostic purposes [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…D'Avino et al. tested a novel NCL‐targeting immunoconjugate (4LB5‐HP‐RNase), engineered by fusion of the novel human anti‐NCL scFv 4LB5 and a human pancreatic RNase, on exosomes from derivatives of colorectal cancer cells (D'avino et al., 2016). Using miR‐21 as readout, their results suggested that, possibly, the binding disruption between NCL and miR‐21, mediated by 4LB5 scFv moiety, allows miR‐21 free‐form to be degraded by the RNase.…”
Section: Nucleolin (Ncl)mentioning
confidence: 99%
“…Early hypotheses focused on digestion, as RNase A is abundant in the pancreas of ruminants (Barnard 1969). This hypothesis is challenged by recent work demonstrating nondigestive activities when human RNase 1 variants and conjugates are administered exogenously in vitro and in vivo (Strong et al 2012;D'Avino et al 2016;Hoang et al 2018).…”
Section: Introductionmentioning
confidence: 99%